The rhetorical density of authorial emotiveness and voice passiveness in abstract compositions - Mohamad, Hairul Azhar; Pilus, Zahariah; Md Zolkapli, Rasyiqah Batrisya; Mohaini, Muhammad Luthfi; Abdul Wahab, Nadiah Hanim; Nath, Pavithran Ravinthra (Asian Economic and Social Society (AESS) Publications, 2023)
The study sought to examine authorial emotiveness and passive tone of academic writing in academic research abstracts (RAs) to appeal to the Aristotelian pathos. Based on the integrated framework of Contrastive Rhetoric and Domain of Emotional Tone, this study investigated the overall demonstration of emotional appeal through quantitative content analysis of two rhetorical items - emotive phrases and passive voice in subtly ‘colouring’ the academic tone of research abstracts. Four hundred eighty (480) research abstracts (RAs) of the international non-native English writers (INE) and Malaysian non-native English writers (MNNE) were sampled from 88 national and international indexed journals. Two quantitative analysis tools were used to autogenerate the frequency percentages, which were then analysed with SPSS. It was found that MNNE RAs showed a significantly denser level of overall emotional appeal than INE RAs. The authorial tones of emotiveness and passiveness were also distinctly heavier in academic MNNE RAs than INE RAs. These were concluded as the marked rhetorical features of non-native English writers, deflecting them from the ones used by native English writers. In terms of research implication, the common trend of these features was not to be misconstrued by MNNE writers as the main rhetorical appeal of research composition.